Interindividual differences in upper limb muscle synergies during baseball throwing motion in male college baseball players - Aoyama, T.; Ae, K.; Kohno, Y. (Journal of Biomechanics, 2022)
Throwing is a fundamental human motor behavior that has evolved to aid hunting and defense against predators. In modern humans, accurate throwing is an important skill required in many sports. However, the spatiotemporal coordination of muscles during baseball throwing has not been fully elucidated. We herein aimed to identify the muscle synergies involved in baseball throwing and determine whether their spatiotemporal patterns are shared among individuals. Ten college baseball players participated in this study. Electromyographic activity was recorded from 13 ipsilateral upper limb muscles during throwing using full effort. Non-negative matrix factorization was used to extract the motor module composition and temporal activation patterns during baseball throwing, followed by k-means analysis to cluster the extracted motor modules based on their similarity. Four motor modules were extracted for each player. These were classified into four clusters (Clusters 1-4), each reaching the peak activity sequentially from the early cocking phase to ball release. Spatiotemporal interindividual similarity in the muscle synergy cluster comprising the muscles activated during the transition from early cocking to late cocking (Cluster 2) was significantly lower than that in the other clusters. There was no individual-specific muscle synergy. These results suggest that the skilled baseball throwing motion acquired through years of practice may consist of four basic muscle synergies that are common among individuals with some differences in their spatiotemporal patterns.